The Leadership Transformation Of Tuan Guru Hj Mohd Yassin: A Case Study In Johor, Malaysia. - Othman Ab. Rahman; Sapora Sipon; Mohd Yahya Arifin (Zes Rokman Resources, 2024)
Journal of Education and Social Sciences, Vol. 5, (October)